Origin of the Autophagosomal Membrane in Plants - Zhuang, Xiaohong; Chung, Kin Pan; Jiang, Liwen (Frontiers in Plant Science, 2016)
During autophagy, cargo molecules destined for degradation are sequestrated into a double membrane structure called autophagosome, which subsequently fuses with the vacuole. An isolation membrane structure (also called the phagophore) initiates from the platform termed PAS (phagophore assembly site or preautophagosomal structure), which then elongates and expands to become the completed autophagosome. The origin of the membrane for autophagosome formation has been extensively investigated but remains an enigma in the field of autophagy. In yeast and mammalian cells multiple membrane sources have been suggested to contribute to autophagosome formation at different steps, from initiation through expansion and maturation. Recent studies in plants have provided a significant advance in our understanding of the conserved role of autophagy and the underlying mechanism for autophagosome formation. Here, we will discuss and evaluate these new findings on autophagosome formation in plants, with a particular focus on the origin of plant autophagosomal membranes.